Prediction of Induced Draft Fan Power Consumption in Thermal Power Plant by using Fuzzy Logic - Pintu Soni (Journal of Power Electronics and Devices, 2019)
The coal fired power plants auxiliary power gulp a large amount (8-13 percent) of generated power here, the excessive auxiliary power by the improper management and usage due to the design and classical equipments of high power ratings, the power generation in a plant is not same/optimum over the day/period, It changes according to the load, so if the auxiliaries run at the maximum load there is a wastage of power during the period of minimum requirement of power. And also induced power fan (ID fan) generally consumes approximate 30-35% of the total power consumption of in house auxiliaries. So in this paper with the help of Fuzzy logic we are going to present a model where the auxiliary power varies simultaneously with the power generation.